Digital Transformation Framework in Consumer Goods Wholesale Industry SMEs : Case Study in Wholesale SMEs of Babelan Districk - Hidayat, Fadli; Hasbullah, Hasbullah; Purba, Humiras Hardi (Politeknik STMI Jakarta, 2024)
Small and Medium Industry (SMEs) is one type of business that has experienced a fairly developed growth valuation. Consumer goods wholesale SMEs have experienced rapid growth in the sales sector, specifically in the Babelan sub-district the consumer goods wholesale industry still uses a manual control system in running its business. The sales process with the Conventional System is carried out starting from stock control, sales activity control, sales process, cashier and revenue generation is still done manually. The manual control process causes a slow counting process, and a long process of re- ordering goods and losing assets. The solution needed at this time is the creation of a framework for Digital Transformation Steps in the sales process to facilitate the control of wholesale consumer goods business processes. The digital transformation framework is expected to modernize the sales process starting from the cashier system, revenue control system, sales activity control process and make it easier for wholesalers to order goods. This applied research is expected to be able to provide suggestions for wholesale consumer goods businesses in running their business in a more efficient and practical direction and can be a recommendation to be able to carry out a digitally transformed sales process.